Simulation of drainage and reuse system for watertable management of canal irrigated areas: a case study - Kumar, Ranvir, author; Singh, Joginder, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
The introduction of canal irrigation in the semi-arid regions of the Haryana State of India underlain with saline ground water in early sixties led to the rise in water levels at an annual rate of 0.3 to 1.0 m and secondary salinization adversely affecting crop production. To develop feasible technologies for the reclamation of such areas, a pilot study on sub-surface tile drainage systems was undertaken in an area at the Haryana Agricultural University Farm having shallow water levels and high salinity. The drains with three spacings (24, 48, 72 m) were placed at a depth of 2.5 m. The water levels, drainage rates and soil salinity data from the study area growing vegetable crops (eggplant, tomato and potato) were used to calibrate the Field Agricultural Irrigation and Drainage Simulation (FAIDS) model for the period 1985-1989 and validate it for the period 1989-93. A number of simulations were also carried out to finalize optimum drain configuration (spacing x depth) under existing agrohydrological conditions. The drain configurations of 75 m x 2 m (1st option) and 100 m x 2.5 m (2nd option) performed equally well based on salinity in the root zone and crop performance. In both the options, relative evapotranspiration (ETa/ETp) of 0.81 was attained during the third year of operation of the drainage system under normal rainfall conditions. The occurrence of a maximum one-day rainfall event (1 in 10 years) during the fifth year resulted in the failure of one out of three crops in both the options in that year indicating the necessity of integration of a surface drainage system with the subsurface drainage under abnormal rainfall events. The existing inland basin drainage conditions did not permit the disposal of drainage effluent. The reuse system was therefore, integrated with the drainage system. A model RESBAL was coupled with the calibrated and validated model FAIDS and run for eight years to optimally design a series of connected reservoirs for the disposal of drainage effluent from an area provided with a subsurface drainage system. The possibility of the reuse of the disposed water for irrigation, aqua culture and salt harvesting was also studied comprehensively in order to maintain proper salt balance in the root zone. On the basis of this study, subsurface drainage systems coupled with surface drainage systems are being extended in Haryana to over 2000 ha of the farmers' land severely affected with waterlogging and soil salinity using a tile-laying trenching machine.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.